2015
DOI: 10.1353/ces.2015.0000
|View full text |Cite
|
Sign up to set email alerts
|

“Teaching Somebody to Fish”: Implications for Immigrant-Serving Organizations and Employment in Edmonton and Winnipeg

Abstract: Provincial governments increasingly develop strategies that attract immigrants to settle in the Prairie Provinces. Although considerable research examines the role of settlement services in larger cities such as Toronto, Montreal, and Vancouver, there is less information regarding mid-sized cities. Increasingly, newcomers are moving to Manitoba and Alberta due to real or perceived economic opportunities. Unfortunately, some immigrants experience difficulties during their settlement process, and their varied ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Once in Canada, however, the men were unable to reconstruct their identities as hard‐working, employed providers. They sought to work or even to volunteer in transitional or entry‐level positions in their areas of training and experience as a bridge to meaningful employment (Thomas, 2015). A national study indicated that Syrian employment rates were lower than that of refugees from other countries and none of our participants had found work a year after arrival (IRCC, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in Canada, however, the men were unable to reconstruct their identities as hard‐working, employed providers. They sought to work or even to volunteer in transitional or entry‐level positions in their areas of training and experience as a bridge to meaningful employment (Thomas, 2015). A national study indicated that Syrian employment rates were lower than that of refugees from other countries and none of our participants had found work a year after arrival (IRCC, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many newcomers understandably feel pressured to secure employment before the cession of their governmental income support (Senthanar et al, 2020). Newcomers are frequently told that “Canadian experience” is a condition for employment, yet they struggle to obtain this work experience due to language barriers, devaluing of their home country credentials and experience, discriminatory reference check practices, lack of Canadian references, the loss of their social networks, different workplace norms, racism and discrimination (George & Chaze, 2014; Hanley et al, 2018; Kosny et al, 2019; Krahn et al, 2000; Schellenberg & Maheux, 2007; Thomas, 2015). These factors may explain why refugees have higher rates of unemployment (Wilkinson & Garcea, 2017) and, if employed, frequently work in precarious, demanding and low‐paying positions (Kosney et al, 2019; Kumar Agrawal, 2019; Senthanar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Government‐funded settlement services are available in cities for areas such as language and skills development, assessments and referrals, community connections, and employment. However, they are primarily delivered by the non‐profit sector based on contractual agreements with the government (Flynn & Bauder, 2015; Shields et al, 2016; Thomas, 2015). Programs are funded on a competitive basis and to be successful require a large network of services (Drolet & Teixeira, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 1967, Canada's immigration policy entailed overt racist preferences for immigrants of white racial origins (Simmons, 2010;Thomas, 2015). With the introduction of the Points System in immigration policy in 1967, the composition of source regions for immigration changed from predominantly Europe and opened up to individuals from all parts of the world, including people from Asia, Latin America, and Africa (Boyd, 2009;Yan et al, 2012).…”
Section: Immigration Policy In Canadamentioning
confidence: 99%
“…In the survey, first, a list of EPS was provided and employment coordinators were asked to check off those services that their employment centre offered. In developing this list, I consulted the literature on employment program and service provision, with a focus on service delivery to newcomers and immigrants and refugees (Canadian Council for Refugees, 1998;Reinberg, 1999;Peera, 2003;Krahn & Taylor, 2005;Shields et al, 2006;Rossiter & Rossiter, 2009;Thomas, 2009;Van Ngo, 2009;Access Alliance, 2011;Froy & Pyne, 2011;States News Service, 2012;Oguz, 2013;BC Centre for Employment Excellence, 2014;Caribbean Development Bank, 2015;Thomas, 2015).…”
Section: Research Instrumentmentioning
confidence: 99%